STRESS ANALYSIS OF SINGLE POINT FIXINGS - Shrivastava, Ashish; Shah, Chirag; Rathore, Peeyush Singh; Jain, Vaibhav (MATTER: International Journal of Science and Technology, 2016)
The paper presents a methodology for assessing the structural integrity of Single Point Fixing (SPF’s) used on a pilot control stick. The main aim is to provide a thorough process by which these SPF’s and the adjoining structure can be assessed for any Active Inceptor System. In this, all the relevant processes are identified including all the possible failure mechanisms.